(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2025)
To evaluate the quality of chocolate produced with Ivorian cocoa beans, the study was carried out in the country’s three main production areas (East, Centre-West, and South-West). The project involved collecting data on fermentation times and sourcing samples of cocoa beans from which chocolate had been produced and tasted. The findings of this study indicate that the average fermentation time for cocoa beans is identical across all regions. The observed values (5.30 days in the East, 5.0 days in the Center-West, and 5.04 days in the South-West) are below the recommended 6-day threshold for optimal fermentation. The chocolate produced from the collected beans has been found to have favourable organoleptic characteristics, as evidenced by the low bitterness ratings revealed in the tasting tests. Acidity and astringency are very low and aroma is average. The correlation study between fermentation time and organoleptic characteristics demonstrated that only bitterness (y = -0.2926x + 4.0115; r = 0.62; p < 0.01) and aroma (y = 0.1619x + 2.1324; r = 0.5139; p < 0.01) of chocolate were significantly influenced by fermentation time. Therefore, cocoa from Côte d’Ivoire is suitable for use in the production of high-quality chocolate. However, fermenting the beans for 6 days would be beneficial to achieve a superior quality chocolate product. Int. J. Agril. Res. Innov. Tech. 14(2): 53-61, December 2024